Socioeconomic Differences in Anthropometric Measurements among School Children Living in Karachi - Hashmi, Ghazal Muzaffar (Nurture, 2007)
Children form different socioeconomic status (SES) is likely to have different measurements. Paucity of local data hinders development of standard size of garments and presence of differences due to income level may further aggravate the problem. This study was conducted among a representative sample of 1498 7-14 year old schoolchildren of Karachi to explore socioeconomic differences in measurements needed for apparel construction.